IoT-Future Smart Systems - Batra, Simple (International Journal of Computer Sciences and Engineering, 2025)
IoT (Internet of Things) is the advanced concept of ICT (Information Communication Technology), connected network of physical objects-devices, vehicles, buildings, machines and sensors. Controlling of remote objects across the distributed network infrastructure and sensing them is done by Internet of Things in which all devices and services in collaboration reduce human involvement for better human life. The Internet of Things (IoT) is the result of integration of fragmented complex technologies to meet the social, economic and business challenges. The Internet revolution has given new approach to business to-consumer (B2C) industries such as media, retail and financial services. In the coming 10 years, the Internet of Things revolution will facilitate and change manufacturing, energy, agriculture, transportation and other industrial sectors to transform how people will work through new interactions between humans and machines. This technological change will bring exceptional opportunities, along with new risks, to business and society.